2016
DOI: 10.3390/atmos7110145
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Optimized WRF Precipitation Forecast over a Complex Topography Region during Flood Season

Abstract: Abstract:In recent years, the Weather Research and Forecast (WRF) model has been utilized to generate quantitative precipitation forecasts with higher spatial and temporal resolutions. However, factors including horizontal resolution, domain size, and the physical parameterization scheme have a strong impact on the dynamic downscaling ability of the WRF model. In this study, the influence of these factors has been analyzed in precipitation forecasting for the Xijiang Basin, southern China-a region with complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 33 publications
3
13
0
Order By: Relevance
“…The statistical results indicate that the model results from the smaller outer domains and shorter lead times perform better statistically than those from larger domains and longer lead times. Goswami et al [13] investigated this issue using >10 km resolutions and the Fifth-generation Penn State/NCAR Mesoscale Model (MM5) simulations for three high-impact weather (heavy rainfall) events over the Tropics to establish the best model performance. Their results showed that domain size is as important as grid spacing and initial conditions in the simulating high-impact weather events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The statistical results indicate that the model results from the smaller outer domains and shorter lead times perform better statistically than those from larger domains and longer lead times. Goswami et al [13] investigated this issue using >10 km resolutions and the Fifth-generation Penn State/NCAR Mesoscale Model (MM5) simulations for three high-impact weather (heavy rainfall) events over the Tropics to establish the best model performance. Their results showed that domain size is as important as grid spacing and initial conditions in the simulating high-impact weather events.…”
Section: Discussionmentioning
confidence: 99%
“…Dravitzki and McGregor [10] investigated heavy rainfall events over the Waikato River Basin of New Zealand generated with higher-resolution WRF, and Goswami et al [11,12] showed that domain size is as important as grid spacing and initial conditions for heavy rainfall events. Additionally, Li et al [13] analyzed the influence of horizontal resolution, domain size, and physical parameterization schemes to evaluate an optimized WRF precipitation forecast over a region of complex topography during the flood season. The research-grade and storm-scaled operational Numerical Weather Prediction (NWP) models of the Korea Meteorology Administration (KMA) regularly produce simulations with a horizontal grid spacing as fine as 1 km over the megacity of Seoul and its surrounding cities, and have been used to obtain new insights to develop a high-resolution model configuration based on WRF [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…A fully compressible, non-hydrostatic dynamic framework is adopted in the ARW module. In recent years, WRF has been widely used in both academic research and industry [32][33][34]. Many studies show that WRF can simulate lower boundary conditions well over complex orography [35,36], which can help WRF to couple with CFD accurately.…”
Section: Wrf Model Setupmentioning
confidence: 99%
“…The NWP model used in this research is the WRF model, which is widely used in the atmospheric and oceanic community. In the present case, we adopted version 3.8 of the Advanced Research WRF (WRF-ARW), which is widely applied in atmospheric and oceanic research [13][14][15]. The WRF-ARW model is driven by the National Centers for Environmental Prediction (NCEP)-NCAR reanalysis data, with a 0.25 • × 0.25 • global latitude-longitude grid.…”
Section: Nwp Model-wrfmentioning
confidence: 99%